Use-Phase Drives Lithium-Ion Battery Life Cycle Environmental Impacts When Used for Frequency Regulation - Ryan, Nicole A; Lin, Yashen; Mitchell-Ward, Noah; Mathieu, Johanna L; Johnson, Jeremiah X (Environmental science & technology, 2018)
Battery storage systems are attractive alternatives to conventional generators for frequency regulation due to their fast response time, high cycle efficiency, flexible scale, and decreasing cost. However, their implementation does not consistently reduce environmental impacts. To assess these impacts, we employed a life cycle assessment (LCA) framework. Our framework couples cradle-to-gate and end-of-life LCA data on lithium-ion batteries with a unit commitment and dispatch model. The model is run on a 9-bus power system with energy storage used for frequency regulation. The addition of energy storage changes generator commitment and dispatch, causing changes in the quantities of each fuel type consumed. This results in increased environmental impacts in most scenarios. The impacts caused by the changes in the power system operation (i.e., use-phase impacts) outweigh upstream and end-of-life impacts in the majority of scenarios analyzed with the magnitude most influenced by electricity mix and fuel price. Of parameters specific to the battery, round trip efficiency has the greatest effect.